Interactional Synchrony in Collaborative Presentations for Students’ Fluency Development - Indriati, Titin; Veniati, Veniati; Krishnaningsih, Shanty Dwi; Dicko, Abdramane; Manto, Manto (Paedagogie, 2026)
This study explores how Collaborative Presentation Tasks facilitate the development of speaking fluency among 54 Electrical Engineering students in an English as a Foreign Language (EFL) context. Adopting a qualitative descriptive design, the study investigated students’ lived experiences of collaborative presentations, with particular attention to the emergence of interactional synchrony during preparation and delivery stages. Data were collected through classroom observations, audio-video recordings of group presentations, semi-structured interviews, and students’ reflective journals. The analysis focused on how coordinated rehearsal, shared cognitive planning, peer scaffolding, and orderly turn-taking evolved within collaborative groups and shaped students’ fluency development. The findings reveal that collaborative presentation environments fostered psychological safety, significantly reducing speaking anxiety and encouraging students’ willingness to communicate and take linguistic risks. Joint rehearsal practices enabled students to align pacing, rhythm, and transitions, resulting in smoother speech flow, fewer hesitation markers, and greater speech automaticity. In addition, collective content construction reduced cognitive load when presenting technical material, allowing students to focus more on meaning delivery and interaction rather than linguistic accuracy. Peer support further promoted more authentic and spontaneous oral expression, although challenges such as unequal participation and reliance on more proficient peers were also observed. Overall, the study demonstrates that collaborative presentations function not only as assessment tasks but as fluency-enhancing learning environments that integrate cognitive, emotional, and interactional support. These findings highlight the pedagogical potential of synchrony-based collaborative speaking activities in engineering education and offer practical implications for designing communication tasks that promote confident, fluent, and meaningful oral communication.